ANALISIS DAN EVALUASI MEDIA E- LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Puspita, Nadia (Institut Syekh Abdul Halim Hasan Binjai, 2023)
The Internet can be used as a way to transfer knowledge from teacher to student. Elearning is one of learning media which uses internet. The purpose of this research is to describe and analyze: (1) the learning planning; (2) the learning process; (3) the learning evaluation; (4) the learning process results of Islamic Education learning with e-learning. This research uses qualitative approach and descriptive method. The data collection technique are interviews, observation, and study of documentation. This research was conducted in one of SMA in Kab. Langkat who have used e-learning as a learning media. Based on the results of the research, it was found that the learning planning of Islamic Education learning with e-learning is not much different with no use of e-learning. The learning implementation process of Islamic Education learning with e-learning is conducted by the method of lecture that assisted with e-learning as a students learning resource centre. Learning evaluation of Islamic Education learning with e-learning is done in the moment after the sub chapter materials have been studied by students with automated systems in e-learning. The results of the learning process of Islamic Education learning with e-learning effect on student learning outcomes. The influence is only experienced on the competence of knowledge, while attitude and skills there is no correlation.